Cholangiocarcinoma - Sarcognato, Samantha; Sacchi, Diana; Fassan, Matteo; Fabris, Luca; Cadamuro, Massimiliano; Zanus, Giacomo; Cataldo, Ivana; Capelli, Paola; Baciorri, Francesca; Cacciatore, Matilde; Guido, Maria (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
Liver cancer represents the third leading cause of cancer-related death worldwide. Cholangiocarcinoma (CCA) is the second most common type of liver cancer after hepatocellular carcinoma, accounting for 10-15% of all primary liver malignancies. Both the incidence and mortality of CCA have been steadily increasing during the last decade. Moreover, most CCAs are diagnosed at an advanced stage, when therapeutic options are very limited. CCA may arise from any tract of the biliary system and it is classified into intrahepatic, perihilar, and distal CCA, according to the anatomical site of origin. This topographical classification also reflects distinct genetic and histological features, risk factors, and clinical outcomes. This review focuses on histopathology of CCA, its differential diagnoses, and its diagnostic pitfalls.